2019
DOI: 10.1111/birt.12467
|View full text |Cite
|
Sign up to set email alerts
|

Preterm births in Iceland 1997‐2016: Preterm birth rates by gestational age groups and type of preterm birth

Abstract: Background The frequency of preterm births has been increasing globally, mainly due to a rise in iatrogenic late preterm births. The aim of this study was to assess the prevalence of preterm births in Iceland during 1997‐2016 by type of preterm birth. Methods This study included all live births in Iceland during 1997‐2016 identified from the Icelandic Medical Birth Registry. Risk of preterm birth by time period was assessed with Poisson regression models adjusted for demographic variables and indications for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
(126 reference statements)
0
5
0
7
Order By: Relevance
“…The effect may be exclusive to prelabor cesarean births. We previously reported on the iatrogenic preterm birth rate in Iceland (induction of labor and prelabor cesarean birth), which has also significantly increased since 1997, despite adjustment for clinical indication groups 20 . For the study reported here, we also adjusted the preterm prelabor CB rate for clinical indication groups, which did not affect the results.…”
Section: Discussionmentioning
confidence: 98%
“…The effect may be exclusive to prelabor cesarean births. We previously reported on the iatrogenic preterm birth rate in Iceland (induction of labor and prelabor cesarean birth), which has also significantly increased since 1997, despite adjustment for clinical indication groups 20 . For the study reported here, we also adjusted the preterm prelabor CB rate for clinical indication groups, which did not affect the results.…”
Section: Discussionmentioning
confidence: 98%
“…Fyrirburafaeðingar eru taldar vera á bilinu 5-18% faeðinga á heimsvísu og þar af eru Norðurlöndin með hvað laegsta tíðni. 13 Meðaltal á heimsvísu er 10,6% 14 en þrátt fyrir að tíðnin hér á landi sé laegri, hafa fyrirburafaeðingar hér á landi aukist úr 4,8% árin 1972-1981 í 6,1% árin 2012-2016. Meirihluti fyrirburafaeðinga fer sjálfkrafa af stað, 15 en tíðni meðferðartengdra fyrirburafaeðinga hefur aukist undanfarin ár vegna sjúkdómsástands móður eða fósturstreitu.…”
Section: Inngangurunclassified
“…Meðferðartengdar fyrirburafaeðingar eru nú um tvöfalt hlutfall af fyrirburafaeðingum á Íslandi miðað við árið 1997, eða 43% af öllum fyrirburafaeðingum. 14 Fylgikvillar fyrirburafaeðinga valda um 35% dauðsfalla hjá nýburum og 16% hjá börnum undir 5 ára aldri. 16 Auk þess kljást fyrirburar við ýmsa kvilla sem eru tengdir því að hafa faeðst fyrir tímann eins og öndunarfaerasjúkdóma, taugakvilla, og sjón-og heyrnarskerðingu.…”
Section: Inngangurunclassified
See 1 more Smart Citation
“…It occurs in 8%-13% of all pregnancies and is a major cause of perinatal mortality and morbidity. It also brings a considerable economic burden to families and society [ 2 ]. As many as 50% of spontaneous PTBs are linked to inflammatory cascades that induce uterine contractions.…”
Section: Introductionmentioning
confidence: 99%